Sodobne oblike metričnega dokumentiranja objektov kulturne dediščine - Kosmatin Fras, Mojca (Geodetski vestnik, 1998)
The paper presents the recent development of the Photogrammetry Department of the Institute of Geodesy and Photogrammetry FGG in the field of metrical documentation of structures which are part of the cultural heritage. Work was focused on developing up-to-date metrical documentation of structures, promoting team work, promoting the use of photogrammetry in the humanities and preparing recommendations for technical standards for structures. A review of the work is supplemented with examples of implemented projects
Keywords: arhitekturna fotogrametrija; fotogrametrija; geodezija; računalniška grafika; Slovenija